DICTIONARY USE AND VOCABULARY CHOICES IN L2 WRITING - Elola, Idoia; Rodríguez-García, Vanessa; Winfrey, Katherine (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In second language (L2) writing research it is essential to focus on the learners’ writing processes to understand their L2 vocabulary use; namely, limitations, choices, and misunderstandings. This article offers an overview of learners’ Spanish-English online dictionary use in relation to L2 writing tasks, the strategies being used, and the limitations encountered while on task. The diverse data collection techniques—written texts, verbal protocols and interviews—provide a holistic view of students of Spanish as a foreign language in their online dictionary use, as well as information about the learners’ reflections on their dictionary use. Results do not only indicate that learners use the dictionary to find a word they did not know, to check their spelling, or to ascertain the meaning of a word, but also to express themselves better or translate the complexity of their English thoughts into Spanish. However, the texts they produced result also from their limited ability in the dictionary use and inability to transfer known strategies from their first language (L1) to their L2. Finally, certain pedagogical implications are discussed to help learners achieve a better command of the dictionary. Resumen En la escritura de una segunda lengua (L2), es esencial concentrarse en los procesos de escritura de los estudiantes para entender el uso de vocabulario en la segunda lengua; principalmente, limitaciones, elecciones, y malentendidos. Este artículo ofrece una visión global del uso que hacen los estudiantes del diccionario español-inglés en Internet en relación a tareas de escritura, estrategias, y las propias limitaciones de los estudiantes. Las diversas técnicas de recogida de datos—textos, protocolos verbales y entrevistas—contribuyen a ofrecer una perspectiva holística del uso de los diccionarios en Internet de los estudiantes de español como lengua extranjera, además de mostrar las reflexiones de los estudiantes sobre su propio uso del diccionario. Los resultados no solamente indican que los estudiantes utilizan el diccionario para encontrar una palabra desconocida, revisar la ortografía, o averiguar el significado de una palabra, sino también para expresarse mejor o traducir la complejidad de sus pensamientos en inglés al español. Sin embargo, los textos reflejan su limitada habilidad con el uso del diccionario y su incapacidad de transferir estrategias de la primera lengua (L1) a la L2. Finalmente, se presentan varias implicaciones pedagógicas para ayudar a los estudiantes a lograr un mejor dominio del diccionario.